Linux under the hood - Vugt, Sander van; Safari eBooks ([Place of publication not identified] : Prentice Hall, 2017)
"Linux Under the Hood is a unique video project that focuses on Linux internals, so you can get the most out of the Linux operating system. Although most Linux books and videos explain how to accomplish tasks in Linux, this video course goes beyond the how and dives into the why. So, instead of learning how to use commands and configure services, you will take a look at what's happening in Linux when you perform tasks. We'll go deeply into the Linux operating system in a way that is understandable to anyone who has already worked a bit with Linux. There's no need to be an expert or have a C programming language background; the only thing that is required is a bit of experience with the Linux operating system and a desire to learn really understand it."--Resource description page.
Title from resource description page (Safari, viewed February 3, 2017).
Presenter, Sander van Vugt.
Keywords: Linux -- Handbooks, manuals, etc; Operating systems (Computers); Electronic books